An Investigatory Project of Banana (Musa) Mibrib as a Commercial Bag: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Banana (Musa) is a popular food crop globally, but diseases like Panama disease can causeserious damage to banana plantations. The resulting waste can be difficult for farmers tomanage. To address this issue, there is an ongoing effort to create commercial paper bagsusing banana fibers from plantation waste. This method can reduce plant wastes from bananaharvesting and decrease the use of plastic bags that pollute the environment.The results of the study in terms of ingredients, procedural process, durability, andpresentation are highly acceptable according to chemical engineers and acceptable accordingto environmental engineers. It indicates that there is no significant difference between andamong the assessments of the two groups of respondents in terms of ingredients, proceduralprocess, durability, and presentation. The mean for the chemical engineers was 2.85, whilethe environmental engineers obtained 2.55. The variance obtained by chemical engineers is2.544, while the variance obtained by environmental engineers is 2.088. The T-computedvalue is 0.316. T-critical is 2.306, with an alpha level of 0.05 and degrees of freedom of 8.Therefore, it accepts Ho. It indicates that there is no significant difference between theassessment of the two groups of respondents in terms of the aforementioned variables.To further enhance this project, it is recommended to gather the banana midrib beforehandand find sources to reduce production costs. Respondents suggested using adhesive, addingextra fabric layers, and using strong stitching materials such as nylon and polyester.Reinforcing the handles with additional stitching or doubling the fiber was also recommended.To make the product more attractive and fashionable, respondents suggested adding colorsand an appealing design.
Keywords: Engineering